Phosphorylation of T-antigen and control T-antigen expression in cells transformed by wild-type and tsA mutants of simian virus 40. - Edwards, C A (1979)
Chinese hamster lung (CHL) cells transformed by wild-type simian virus 40 (cell line CHLWT15) or transformed by the simian virus 40 mutants tsA30 (cell lines CHLA30L1 and CHLA30L2) or tsA239 (cell line CHLA239L1) were used to determine the rates of turnover and synthesis of the T-antigen protein and the rate of turnover of the phosphate group(s) attached to the T-antigen at both the permissive and restrictive temperatures. The phosphate group turned over several times within the lifetime of the protein to which it was attached, with the exception of the phosphate group in the tsA transformants at 40 degrees C, which turned over at the same rate as the T-antigen protein. The steady-state levels of the T-antigens (molecular weights, 92,000 [92K] and 17K) and the amount of simian virus 40-specific RNA was also determined in each of the lines. The CHLA30L1 line contained two to three times more early simian virus 40 RNA than the CHLA30L2 line; although neither line formed colonies in agar at 40 degrees C, CHLA30L1 overgrew a normal monolayer at 40 degrees C. The rate of 92K-T-antigen synthesis was 1.5 times faster in CHLA30L1 than in CHLA30L2 at 33 degrees C and 4 times faster at 40 degrees C. The different phenotype of these two presumably isogenic cell lines seem to be related to the levels of the T-antigens. The ratios of the 92K T-antigen to the 17K T-antigens were similar in the two lines. Transformed CHL cell lines, unlike transformed mouse 3T3 cell lines, were found to contain very small amounts of the 56K T-antigen.